Shortterm and long-term results of bimammary bypass surgery in patients with multivessel coronary disease and type 2 diabetes mellitus after propensity score matching - A. G. Muradov; Yu. I. Grinshtein; D. B. Drobot; A. Yu. Miller; V. A. Sakovich (Acta Biomedica Scientifica, 2023)
Background. Among patients who have undergone coronary artery bypass surgery (CABG), the proportion of people with diabetes mellitus (DM) is about 40 %. To date, the problem of choosing the optimal method of surgical myocardial revascularization, which can provide the best result in this cohort, remains completely unresolved. The aim of the study. To assess the in-hospital and long-term results of bimammary and traditional bypass surgery in patients with type 2 diabetes mellitus. Methods. From September 2018 to December 2021, 176 CABG surgeries were performed in patients with coronary heart disease (CHD) and type 2 diabetes at the Federal Center for Cardiovascular Surgery (Krasnoyarsk). Group 1 (n = 45) included patients who underwent myocardial revascularization using two mammary arteries; group 2 (n = 131) included patients who underwent myocardial revascularization using traditional technique. After propensity score matching, 45 patients were selected into each group, comparable by basic preoperative characteristics. Results. In group  1, cardiopulmonary bypass surgeries were performed in 23 (51.1 %) patients (group 1CPB), off-pump surgeries – in 22 (58.2 %) (group 1OP); in group  2, all patients underwent cardiopulmonary bypass surgeries. Hospital mortality was recorded in group 2 in 1 (2.2 %) case. Deep sternal infection developed in 1 (4.5 %) patient in group 1OP. Long-term survival in group 2 was 85.3 %, in group 1CPB – 83.3 % (p = 0.689), in group 1OP – 84.2 % (p = 0.739). 84.2 % of patients in group 2 and 100 % in groups 1CPB and 1OP had no cardiovascular events (p = 0.144 and p = 0.145, respectively). Conclusion. Bimammary bypass surgery in patients with type 2 diabetes is a safe and effective method of surgical treatment of coronary artery disease in both shortand long-term period and may be the operation of choice in patients with multivessel disease. There were no differences in patient survival up to 45 months; bimammary revascularization was associated with 100 % absence of cardiac mortality.